Self-Reported Personal Hygiene Practices and Associated Factors among Prison Inmates in a Jail in Pakistan - Minahil Nisar; Fatima Soomro; Farhat Jokhio; . Hunebia; Nudrat Zeba; Zubairuddin Qureshi; Syed Ali Naqvi (Pakistan Journal of Health Sciences, 2026)
Prison inmates are a vulnerable population with increased risk of exposure to poor water, sanitation, and hygiene (WASH) conditions, which raises communicable diseases. Objective: To determine self-reported personal hygiene practices and associated factors among inmates in Nara Jail, Hyderabad. Methods: This institution-based cross-sectional observational study was conducted at Nara Jail, Hyderabad (December 2025–January 2026). Ninety-one inmates were selected through simple random sampling. Data were collected using a structured interviewer-administered questionnaire and a standardized observational checklist adapted from WHO WASH guidelines. Associations were analyzed using Chi-square or Fisher’s exact tests, with statistical significance set at p